2017
DOI: 10.1016/j.ejogrb.2017.03.029
|View full text |Cite
|
Sign up to set email alerts
|

A model to evaluate the costs and clinical effectiveness of human papilloma virus screening compared with annual papanicolaou cytology in Germany

Abstract: Screening strategies including primary HPV testing for high-risk subtypes (HPV-16/18) in conjunction with p16/Ki-67 dual-stained cytology can improve the detection of cervical cancer at a lower total annual cost than conventional Pap cytology screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…It improves the detection of CIN2-3 and CxCa, displays better clinical outcomes and creates substantial cost-savings for the Portuguese healthcare system. The results are in line with similar health economic outcome research (HECON) studies [36][37][38][39] and support the current clinical consensus on the move towards molecular screening for cervical cancer not just in Portugal but also other European countries. Nevertheless, as this study is based on a computer-based model cohort, a randomized clinical trial or real-world studies with randomized samples and appropriate methodologies are needed as further research to generalize these results to the population.…”
Section: Discussionsupporting
confidence: 88%
“…It improves the detection of CIN2-3 and CxCa, displays better clinical outcomes and creates substantial cost-savings for the Portuguese healthcare system. The results are in line with similar health economic outcome research (HECON) studies [36][37][38][39] and support the current clinical consensus on the move towards molecular screening for cervical cancer not just in Portugal but also other European countries. Nevertheless, as this study is based on a computer-based model cohort, a randomized clinical trial or real-world studies with randomized samples and appropriate methodologies are needed as further research to generalize these results to the population.…”
Section: Discussionsupporting
confidence: 88%
“…A German study that assessed costs and clinical effectiveness showed that HR-HPV (HPV 16/18) tests performed in conjunction with p16/Ki-67 dual-stained cytology can improve the detection rate of cervical cancer compared to the Pap test alone, with lower total annual cost. 33 In addition, an Australian study demonstrated that HPV tests performed every 5 years are more effective for cervical cancer screening and cost-savings than Pap tests performed every 2 years. This Australian National Cervical Screening Program switched to primary HPV screening with partial genotyping as of 2017.…”
Section: Current Status Of Cervical Cancer Screeningmentioning
confidence: 99%
“…Gardasil (Merck, NJ, USA) showed limited effects against specific viruses including HPV 6,11,16, and 18. Gardasil 9 (Merck) showed limited effects against HPV 6,11,16,18,31,33,45,52, and 58, while Cervarix (GSK, London, UK) showed limited effects against HPV 16 and 18. HPV types 16 and 18 account for between 55% and 70% of cancers and mainly cause cervical cancers.…”
Section: Future Perspectives On Cervical Cancer Screening In Koreamentioning
confidence: 99%
“…In Germany, a recent study revealed that combined HPV 16/18 testing and p16/Ki-67 resulted in lower cost and clinically efficient CC screening, compared with conventional annual Pap cytology [76]. As described earlier, several evidences on the utility of p16/ Ki-67 have accumulated; therefore, p16/Ki-67 will definitely play an important role in the secondary prevention of CC.…”
Section: Ink4amentioning
confidence: 99%